Tag and Intersentential Code Switching Found in English Young Learners Classroom Interaction - Lopa Dinata; Ardayati Ardayati; Yulfi Yulfi (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
The objective of the research was to describe tag and intersentential code switching found in English young learners classroom interaction at Ganesha English Courses Lubuklinggau. The research questions in this research was they were what were tag and intersentential code switching found in English young learners classroom interaction. Setting of this research were Ganesha English Courses Lubuklinggau. The qualitative approach in descriptive qualitative research design was used in this research because the data was in the form of words rather than the number. The data were collected by means of the observation and interviews. Then the data were analyzed by using transcribing and analyzing. The result of this research show, there were found 31 data; (1) 15 tag codes switching, and (2) 16 intersentential codes switching.